Study of pain perception under negative emotions and its large-scale brain network dynamics in adolescents with non-suicidal self-injury - Zhou, Yang; Zhou, Dongdong; Zhang, Zhengyong; Jia, Huiyu; Chen, Fang; Ran, Liuyi; Chen, Xiaorong; Wan, Liyang; Wang, Yijia; Wang, Wo (Frontiers in Psychiatry, 2025)
BackgroundPrevious studies have indicated that negative emotions are one of the primary causes of non-suicidal self-injury (NSSI) behavior. This study focuses on examining the characteristics of large-scale brain network dynamics associated with pain perception in NSSI adolescents following experiences of negative emotions.MethodsA total of 44 adolescents with Major Depressive Disorder (MDD) and NSSI (MDD+NSSI group), 21 MDD adolescents without NSSI (MDD group), and 25 healthy controls (HC group) were recruited. Two emotional conditions (neutral and negative) were established, followed by the simulation of pain conditions using ice water stimulation, while electroencephalogram (EEG) signals were recorded using a 64-channel EEG system. Statistical analysis was conducted using mixed-design repeated measures analysis of variance, with multiple comparisons corrected using the Bonferroni method.ResultsIn the MDD+NSSI group, after sadness induction, the duration, time coverage of microstate A, and the transition rate from microstate B→A during the Cold Pressor Test (CPT) were significantly higher compared to neutral emotion induction. Conversely, the occurrence frequency of microstate B decreased markedly. Under neutral emotion induction, the MDD group exhibited higher occurrence frequency of microstate A and transition rate from microstate D→A than the HC group. In contrast, the occurrence frequency, coverage of microstate B, and transition probabilities from microstates C/D→B were significantly lower in the MDD group than in the HC group.ConclusionOur findings suggest that adolescents with MDD who exhibit NSSI behavior display abnormalities in large-scale brain network dynamics associated with pain perception following experiences of negative emotions, indicating that EEG microstates may serve as neurobiological markers for abnormal pain perception in NSSI adolescents.